Blood biomarkers for differential diagnosis and early detection of pancreatic cancer - Al-Shaheri, Fawaz N.; Alhamdani, Mohamed Saiel Saeed; Bauer, Andrea; Giese, Nathalia; Büchler, Markus W.; Hackert, Thilo; Hoheisel, Jörg D. (Cancer treatment reviews, 2021)
Pancreatic cancer is currently the most lethal tumor entity and case numbers are rising. It will soon be the second most frequent cause of cancer-related death in the Western world. Mortality is close to incidence and patient survival after diagnosis stands at about five months. Blood-based diagnostics could be one crucial factor for improving this dismal situation and is at a stage that could make this possible. Here, we are reviewing the current state of affairs with its problems and promises, looking at various molecule types. Reported results are evaluated in the overall context. Also, we are proposing steps toward clinical utility that should advance the development toward clinical application by improving biomarker quality but also by defining distinct clinical objectives and the respective diagnostic accuracies required to achieve them. Many of the discussed points and conclusions are highly relevant to other solid tumors, too.